Computational psychiatry : mathematical modeling of mental illness - Anticevic, Alan; Murray, John D. (John David) (Academic Press, 2018)
This book provides readers with a comprehensive survey of work from leading scholars in the field of computational psychiatry, and presents a detailed analysis of the computational methods used in the service of understanding neuropsychiatric symptoms, improving diagnosis and guiding treatments.